Answered

Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

expand and simplify (x-5)(x+2)

Sagot :

(x-5)(x+2)=x^2+2x-5x-10=x^2-3x-10
AyaZ
[tex](x-5)(x+2) \\ =(x*x)+(x*2)+((-5)*x)+((-5)*2) \\ = x^{2} +2x-5x-10 \\ = x^{2} -3x-10[/tex]